2012
DOI: 10.1088/1009-0630/14/5/13
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Dipole Band in113In

Abstract: High spin states in the odd-A nucleus 113 In have been investigated using the reaction 110 Pd(7 Li, 4n) at a beam energy of 50 MeV. A new positive parity dipole band with the configuration of π(g 9/2) −1 ν(h 11/2) 2 ν(g 7/2) 2 is established. The effective interaction V (θ) values of this band have been successfully described by a semiclassical geometric model based on shear mechanism, which show that the dipole band has the characteristics of magnetic rotation. In addition the collective rotational angular mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…For example, the stress-strain curve of the LFWed joint lies inbetween those of the two BMs of TC11 and TC17 alloys. Wen et al [42] and Ma et al [36] also found the similar phenomena on the LFWed joint of Ti-6Al-4V and Ti-6.5Al-3.5Mo-1.5Zr-0.3Si alloys. Fig.…”
Section: Effect Of Strain Rate On the Ys And Utssupporting
confidence: 52%
See 1 more Smart Citation
“…For example, the stress-strain curve of the LFWed joint lies inbetween those of the two BMs of TC11 and TC17 alloys. Wen et al [42] and Ma et al [36] also found the similar phenomena on the LFWed joint of Ti-6Al-4V and Ti-6.5Al-3.5Mo-1.5Zr-0.3Si alloys. Fig.…”
Section: Effect Of Strain Rate On the Ys And Utssupporting
confidence: 52%
“…In the center zone of the joint, the appreciably higher hardness value on the TC11 side of WZ which is obviously attributed to the grain refinement and fine martensites α 0 and α″, and lower hardness value on the TC17 side of WZ, which is ascribed to relatively soft and coarse β phase as shown in Fig. 2 (b) and (c) [27,36]. It is also observed that the hardness value declines gradually from the weld centerline to TC11 BM due to dropping temperature and martensite from the welding line.…”
Section: Microhardnessmentioning
confidence: 92%
“…Wang et al . 7,8 reported their experience on slab corner temperature control and reducing transverse cracks by means of using the asymmetric nozzles. However, the secondary cooling nozzle type and its arrangement should be modified according to the specific casting conditions such as casting speed, slab width, and so on.…”
Section: Introductionmentioning
confidence: 99%